EDUCATION SYSTEMS OF THE KINGDOM OF SAUDI ARABIA AND JORDAN - Ganiyev Avazbek Oybekovich (Bright Mind Publishing, 2025)
This article provides a brief overview of the education systems in the Kingdom of Saudi Arabia and the Hashemite Kingdom of Jordan. It provides a brief history of the education systems in these countries and highlights modern higher education institutions.
Keywords: The education system in the Kingdom of Saudi Arabia, King Saud University, the education system in Jordan, Al-Hussein Bin Talal University, University of Jordan.